Pengetahuan Kontrasepsi Pada Mahasiswa Kesehatan Dan Non-Kesehatan Terhadap Perilaku Penggunaan Kontrasepsi - Febriani, Heni (Jurnal Kesehatan Masyarakat, 2014)
Background: as many as one million women in Indonesia each year experiencing unwanted pregnancies. Family planning counselling Data gathering of the Yogyakarta special region, mention pregnancy outside of marriage during 2007 as much as 460 cases and 30 cases has increased from 2006. One of the factors which aspects influenced the Pregnancy was not expected was the lack of knowledge of contraception and sexual behavior that can lead to pregnancy. Knowledge about contraception for adolescents should be given as early as possible so that they can know clearly whats called contraception. Objective: to know the difference in level of knowledge on health majors with non-contraceptive use behavior towards health. Methods : This study used a cross - sectional design. Population and research subjects were students at Gadjah Mada University Department of health and non-health that as many as 688 randomly selected people. Measuring instruments used questionnaires. Analysis of the data used include : analysis of a univariate, bivariate, and multivariate. Statistical tests using Chi - Square ( X2 ) and ordinal logistic regression with a significance level of p